Experimental investigation for reverse heat transfer in structural fire-protective clothing. Issue 5 (March 2018) - Lee, Duck Weon; Jin, Joon-Hyung; Kim, Eunae; Lee, Junghan
Structural fire-protective clothing must be effective at minimizing the thermal effects of fire. However, water remaining on the outer shell might play an important role in conducting heat transfer, which causes skin burns in a firefighter when he douses a fire with water through a hose. Therefore, this research demonstrated the difference in the heat transfer and humidity created by the remaining water or lack of water on the outer shell under a condition in which the temperature (45 ± 1℃) of the external environment was higher than that of the skin. Two types of multilayered systems, which simulated real fire-protective clothing (outer shell, moisture barrier, thermal liner) were tested by using a human–clothing–environment (HCE) simulator. The experimental results verified that water on the outer shell increased the microclimate temperature in the structural fire-protective clothing. In particular, we assume that air permeability in the outer shell can be an important factor to control heat and mass transfer within the microclimate.